2019
DOI: 10.1111/gtc.12674
|View full text |Cite
|
Sign up to set email alerts
|

Spironolactone‐induced XPB degradation depends on CDK7 kinase and SCFFBXL18 E3 ligase

Abstract: The multisubunit complex transcription factor IIH (TFIIH) has dual functions in transcriptional initiation and nucleotide excision repair (NER). TFIIH is comprised of two subcomplexes, the core subcomplex (seven subunits) including XPB and XPD helicases and the cyclin‐dependent kinase (CDK)‐activating kinase (CAK) subcomplex (three subunits) containing CDK7 kinase. Recently, it has been reported that spironolactone, an anti‐aldosterone drug, inhibits cellular NER by inducing proteasomal degradation of XPB and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 48 publications
6
29
0
Order By: Relevance
“…This is due to spironolactone reversibly inducing the degradation of XPB in a ubiquitin-activating enzyme-and proteasome-dependent manner, impairing both basal and activated mRNA transcription of the transcription/repair factor TFIIH. 374,375 In agreement with this, a recent study also demonstrated that spironolactone could inhibit SIRT2-mediated transcription-coupled nucleotide excision repair, disturbing cisplatin-induced DNA crosslinks in lung cancer. 376 In addition, the function of spironolactone on reducing homology directed repair frequencies was confirmed.…”
Section: Non-oncology Drugs In Drug Repurposingsupporting
confidence: 63%
“…This is due to spironolactone reversibly inducing the degradation of XPB in a ubiquitin-activating enzyme-and proteasome-dependent manner, impairing both basal and activated mRNA transcription of the transcription/repair factor TFIIH. 374,375 In agreement with this, a recent study also demonstrated that spironolactone could inhibit SIRT2-mediated transcription-coupled nucleotide excision repair, disturbing cisplatin-induced DNA crosslinks in lung cancer. 376 In addition, the function of spironolactone on reducing homology directed repair frequencies was confirmed.…”
Section: Non-oncology Drugs In Drug Repurposingsupporting
confidence: 63%
“…Moreover, to discriminate between endogenous and overexpressed XPB, an XPB-GFP construct was used and its impact compared to that of XPD-GFP. Importantly, fusion to green fluorescent protein (GFP) was previously shown to preserve incorporation into TFIIH and activities of both XPB and XPD (31,41). In addition, we found that XPB-GFP retained the ability to coprecipitate with Tax (Fig.…”
Section: Fig 1 Xpb Binds To Tax (A)mentioning
confidence: 62%
“…Strikingly, SP is believed to induce the degradation of XPB within preformed TFIIH complexes, removing XPB while preserving TFIIH integrity (21,30). A recent study showing that SP-induced XPB degradation depends on its prior phosphorylation by the other TFIIH subunit CDK7 provides the molecular explanation for this selectivity (31).…”
mentioning
confidence: 99%
“…In fact, blocking transcription induces apoptosis in proliferative cells but does not spare non-malignant cells, which may suffer from this kind of treatments. Specifically, two drugs have been developed to target TFIIH: (i) triptolide that covalently binds to the XPB subunit of TFIIH and inhibits its ATPase activity [33], triggering CDK7-dependent degradation [24] and hence disrupting both RNAP2 and RNAP1 transcription [37]; (ii) spironolactone that induces XPB degradation [1, 34]. Nevertheless, these drugs have the same drawbacks as other drugs blocking transcription since their use may hinder the cellular activities of normal non-malignant cells.…”
Section: Discussionmentioning
confidence: 99%